Relevance Of Boards and Charts in Contemporary Instructional Delivery in Gokana, Rivers State, Nigeria - Ozioma, Chigbu Prince (International Journal on Integrated Education, 2025)
This study examines the continued relevance and importance of chalkboards and charts as instructional materials in modern classrooms, particularly for effective teaching in resource-constrained areas. Despite advancements in technology and the rise of computer-based instruction, these traditional tools remain indispensable, especially in rural settings where access to electricity and innovative teaching media is limited. A library-based research method was employed, reviewing the perspectives of educationists and technologists on the enduring utility of chalkboards and charts. Key findings highlight the advantages, disadvantages, and practical applications of these tools in classrooms, emphasizing their role as cost-effective alternatives during power outages or in underserved regions. Field observations in Gokana, Rivers State, Nigeria, revealed the persistent reliance on these materials due to infrastructural and financial challenges. The study concludes that chalkboards and charts remain critical for achieving learning objectives in rural education and recommends their continued use alongside efforts to integrate innovative teaching methods.